Bullying and harassment at work. A guide for trade union reps (London, 2015)
"Bullying and harassment are workplace hazards which have grown steadily over recent years to become a top concern for trade union reps. Bullying thrives in conditions of uncertainty and the current financial climate and job insecurity is making people fearful of standing up to the problem. This updated LRD guide provides trade union reps with examples of best practice and practical guidance on what they can do to prevent bullying and harassment in the workplace, how they can confront problems, and how they can best provide support and representation for members who have been bullied and/or harassed."